Calibration and testing of a mechatronic positioning jig for g-induced loss of consciousness - Anitha, Krishnasamy (2013)
Gravity Induced Loss of Consciousness (G-LOC) has always been a problem for the pilots of high performance aircrafts and research has been going on for more than 80 years in this area. During G-LOC, pilots suffer from physiological symptoms like grey out, black out and complete loss of consciousness due to reduced blood flow to brain. The cerebral blood flow is considered to be an important indicator for the occurrence of loss of consciousness. An ultrasound image of the carotid arteries at the side of the neck provides the information about the structure of blood vessels and also blood flow to the brain. Doppler ultrasound is a technique that provides change in flow velocity and blood flow volume through major arteries and veins. The phantom study was carried out to test the efficiency of Doppler ultrasound for the determination of cerebral blood flow volume. The positioning of ultrasound probe is vital for the determination of flow profile. Hence a positioning system designed by Biomechatronics group, NTU was used for positioning the probe to target.